Impact of the Rule of Law as a Fundamental Public Governance Principle on Administrative Law Interpretation in the Czech Republic - Jana Janderová (Central European Public Administration Review)
The rule of law is a fundamental principle and the cornerstone of Western democracies and their public governance. Its underlying value is the idea of constraint of governmental power. The rule of law principle acts as an interpretative concept in most contexts of the exercise of public powers in the EU and its Member States, with the courts exercising supervision over the activities of administrative bodies. However, the teleological argumentation through fundamental principles is not inherent to all Central and Eastern European judicial and administrative bodies, given the long tradition of formalistic approach in most of them. The article analyses whether the approach has changed during the past thirty years and to which level the principle of the rule of law is used for interpretation of administrative law provisions by courts in the Czech Republic. Since the case law of the Czech Constitutional Court and the Czech Supreme Administrative Court is based on the arguments of legality and proportionality as the key elements of the rule of law, their cases were analysed using a comparative method. The article identifies a general tendency in legally difficult cases to move from purely linguistic interpretation to interpretation through values, including the rule of law. Most of the analysed cases reveal that the formalistic interpretation was strongly criticised by both the Constitutional and the Supreme Administrative courts. However, slight differences in their perception of the principles of legality and proportionality were discerned, namely in the debate on the intensity of control exercised by administrative courts over factual and discretionary decisions by administrative authorities. Nevertheless, these differences produce beneficial effects, as both principles continue being developed thanks to the exchange of opinions between the courts. Further research could be conducted for similar countries in the region.